The Institutional Structural Model For Sustainable Maritime Tourism In The Seribu Islands National Parks: An Institutional Analysis - Noviana, Linda; Tatan; Kholil; Sukwika, Tatan (Jurnal Ekologi, Masyarakat dan Sains, 2025)
The Seribu Islands National Park, located north of Jakarta, is a primary marine tourism destination with its beautiful coral reefs as the main attraction. However, the increasing number of visitors is negatively impacting the coral reefs. To mitigate these effects, the role of stakeholders is crucial. Six institutions manage this area: the Seribu Islands National Park Authority (BTNKS), the local government, the tourism office, local communities, entrepreneurs, and NGOs. However, these six institutions do not collaborate harmoniously and often experience overlapping functions. This study aims to analyze the appropriate institutional framework for sustainable marine tourism management using interpretative structural modeling (ISM) with data from expert discussions. The results indicate that BTNKS, the Seribu Islands Regency Government, and the Tourism Office play significant roles. The main challenges that must be addressed urgently include weak inter-institutional coordination, ineffective law enforcement, and inadequate knowledge among tour guides. The necessary program involves building coordination and partnerships, as well as developing the capacity of tour guides.